Constructing a security community in Southeast Asia : ASEAN and the problem of regional order - Acharya, Amitav (London : Routledge, 2014)
'In this third edition of Constructing a Security Community in Southeast Asia, Amitav Acharya offers a comprehensive and critical account of the evolution of the Association of Southeast Asian Nations (ASEAN) norms and the viability of the ASEAN way of conflict management. Building on the framework from the first edition, which inspired the establishment the ASEAN Political-Security community, this new edition has been extensively updated and revised based on new primary sources that are not publicly available.Updates for this edition include:Expanded and updated coverage of the South China Sea Conflict and how it affects regional order and tests ASEAN unityAnalysis of new developments in US role in the region, including ASEAN's place and role in the US pivot/rebalancing strategy and the evolution of the East Asian Community, the newest summit level multilateral groupExtensive analysis of the ASEAN Political-Security communityAn examination of US-China relations and China-ASEAN relationsCoverage of ASEAN's institutional development and the controversy over reform of the ASEAN Secretariat.An updated outlook on ASEAN's future as a security community and the issue of ASEAN Centrality in the regional security architecture. The new edition will continue to appeal to students and scholars of Asian security, international relations theory and Southeast Asian studies as well as policymakers and the media'--
Includes bibliographical references (pages 269-275) and index.
Keywords: ASEAN; National security -- Southeast Asia; Southeast Asia -- Politics and government -- 1945-; Southeast Asia -- Foreign relations